انسانی خدمات میں غیر جانبداری کا تصور سیرت طیبہ ﷺ کی روشنی میں (Khairulummah, 2023)
Religions are created for serving the humanity.Without the existence of human there had not been the religions.Islam while serving the human rights cause get special attention because Islam is widely applauded by the eastern and western rights due to addressing the human problems.Prophet Mohammad S A A W W stsrted his preaching by empowering the status of women by giving them equal status , giving them their share in property, and evidence.Women used to come to mosques and were allowed to business.Prophet Muhaamed eliminated the discrimination on the basis of class, clour, race and gender.He advocated for the rights of labour by emphasizing their true wage on the right time.He participated himself in physical labour in construction of mosques and digging the ditches.His kindness behavior from children to elder persons. He gave special attentions to orphans and needy persons.His last sermon Hujjatul widda which is popularly known as Universal Declaration of human rights. In this sermon he did not talk about the spiritual worship of God but he only talked about humans rights and like wise serving human cause is understood as a worship of God.
Keywords: Human, Services, Rights, Values, Seerat